PO207 Thromboembolic risk in inflammatory neuromuscular disease patients on long-term ivig. (1st December 2017) - Spillane, J; Englezou, C; Sarri-Gonzalez, S; Rossor, A; Lunn, MP; Manji, H; Reilly, MM; Carr, AS
Abstract : Background: Observational data suggest intravenous immunoglobulin (IVIg) increases risk of thromboembolic events (TEE). Traditional vascular risk factors influence individual risk but the pro-coagulant mechanism of IVIg is not understood. Aims: To ascertain frequency of and risk factors for arterial (ATE) and venous thromboembolic events (VTE) in neuromuscular patients receiving regular IVIg. Methods: Diagnosis, dose, frequency, vascular risk factors, pre and post-treatment IgG levels and plasma viscosity were recorded by retrospective casenote review. Results: 112 patients received a mean (S.D) dose of 1.6 (1.2)g/kg/month, range:0.2–6.5 g/kg/month; at a mean (S.D.) interval of 4.4 (3.0) weeks, range:1–18 weeks for CIDP (58.9%), MMN (36.6%), sensory neuropathy/neuronopathy (3.7%) and myositis (0.9%). Twelve TEEs were documented during the 30 month study period (January '14-June '16); 6 MIs, 2 CVAs, and individual occurrences of TIA, DVT, PE, SVC obstruction due to central line thrombosis. TEE incidence (95% C.I.)=53.6 (30.9, 91.3)/1000 patient-years; ATE incidence=35.7 (18.2, 68.9)/1000 patient-years; VTE=22.3 (9.6–51.2)/1000 patient-years. Age (p=0.005) and QRISK2 score (p=0.01) were higher in those who had an event. There was no difference in dose/kg/month (p=0.66), or dose/g/day (p=0.28). Conclusions: TEE incidence in this cohort was higher than population-based rates (TEE=7.6–7.7/1000; ATE=4.4–6.5/1000 and VTE=1.2/1000 patient-years). This analysis suggests reduction of daily dose or rate of infusion does little to mediate risk.